The wake-up call why the pandemic has exposed the weakness of the West - and how to fix it - Micklethwait, John 1962-; Wooldridge, Adrian (Short Books, 2020)
"In this urgent, beautifully crafted essay, Micklethwait and Wooldridge explain how we ended up in this mess [i.e., the COVID-19 pandemic] and explore the possible routes out of it. They show how Western governments could still combine the best lessons from history with the full potential of technology to reverse this decline. But they also serve warning that if the West continues to turn away from modernity and progress, the prospect of a new Eastern-dominated world order will become almost inevitable."--Front jacket
Keywords: Pandemie; COVID-19; Krise; Weltordnung; Regierung; Bewältigung; Asien; USA; Westliche Welt; Großbritannien; Comparative government; COVID-19 (Disease); Quarantine / Political aspects / Western countries / History / 21st century; Quarantine / Political aspects / East Asia / History / 21st century; Western countries / Politics and government / 21st century; East Asia / Politics and government / 21st century; Epidemics; Public health; Politics and government; East Asia; Western countries; 2000-2099; History